Cigarette smoking status has a modifying effect on the association between polymorphisms in KALRN and measures of cardiovascular risk in the diabetes heart study - Rudock, Megan E.; Cox, Amanda. J.; Ziegler, Julie T.; Lehtinen, Allison B.; Connelly, Jessica J.; Freedman, Barry I.; Carr, J. Jeffrey; Langefeld, Carl D.; Hauser, Elizabeth R.; Horne, Benjamin D.; Bowden, Donald W. (Genes & genomics, 2011)
All manifestations of cardiovascular disease (CVD) are substantially more common in patients with type 2 diabetes mellitus (T2DM) than in non-diabetic individuals. The current study evaluated KALRN , a gene previously linked to CVD, as a contributor to CVD in a sample enriched for T2DM. Specifically, the potential modifying effect of cigarette smoking was examined. A total of 28 SNPs in KALRN were genotyped in 1001 European Americans from 369 Diabetes Heart Study (DHS) families, as well as 762 population-based controls. The association between each SNP and both qualitative and quantitative CVD disease phenotypes was determined using generalized estimating equations and variance component models, respectively. Selected KALRN SNPs were found to be associated with both the qualitative (T2DM, CVD, metabolic syndrome) and quantitative traits (C-reactive protein and abdominal aortic calcified plaque). Interaction analysis and stratification were then used to test whether smoking modulates the genetic effects of KALRN . The strongest evidence of a modifying effect of smoking status was observed for rs9289231 and intima-media thickness (p=9.0x10 −4 ) and abdominal aortic calcified plaque (p=3.0×10 −4 ). Overall, following stratification by smoking status, the evidence of association with quantitative traits was more pronounced in smokers compared to non-smokers. The strongest association for smokers was between rs1720960 and abdominal aortic calcified plaque (p=2.6x10 −5 ), while in non-smokers there was no observed association. KALRN variants are associated with measures of CVD and T2DM in the DHS sample with smoking status observed to have a significant modifying effect on these associations.